2004
DOI: 10.1007/s00223-003-0069-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving Metabolic Control Reverses the Histomorphometric and Biomechanical Abnormalities of an Experimentally Induced Bone Defect in Spontaneously Diabetic Rats

Abstract: Insulin-dependent type 1 diabetes mellitus (IDDM) has been shown to alter the properties of bone and to impair fracture-healing in both humans and animals. The objective of this study was to examine changes in the histomorphometric and mechanical parameters of bone and remodeling during bone-defect healing, depending on the diabetic metabolic state in spontaneously diabetic BB/O(ttawa)K(arlsburg) rats, a rat strain that represents a close homology to IDDM in humans. A standardized bone-defect model was chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 46 publications
6
24
0
Order By: Relevance
“…1). The uncontrolled streptozotocin-induced diabetic disease process weakened the intact contralateral femurs during the 6-week study, similar to other diabetic models [10][11][12]24]. The mean torque to failure of the intact femurs in the nondiabetic group at 4 weeks was 1.6 to 2.1 times greater (p \ 0.009 for all comparisons) than the failure torques of the intact femurs in the three diabetic treatment groups ( Table 3).…”
Section: Resultssupporting
confidence: 70%
“…1). The uncontrolled streptozotocin-induced diabetic disease process weakened the intact contralateral femurs during the 6-week study, similar to other diabetic models [10][11][12]24]. The mean torque to failure of the intact femurs in the nondiabetic group at 4 weeks was 1.6 to 2.1 times greater (p \ 0.009 for all comparisons) than the failure torques of the intact femurs in the three diabetic treatment groups ( Table 3).…”
Section: Resultssupporting
confidence: 70%
“…It has also been reported that systemic insulin treatment reverses this impaired bone healing (Macey et al 1989, Follak et al 2004. However, these studies do not discriminate between a direct effect of insulin on the bone and indirect systemic effects on skeletal metabolism.…”
Section: Postoperative Insulin Resistancementioning
confidence: 99%
“…Diabetes has been characterized as a disease of low bone turnover both by histomorphometry in rodent studies (11,12,13,14,15) and in two studies in human subjects (one involving six patients with T2D, two patients with T1D, and the other involving five patients with T2D and four controls) (16,17). However, another study in 18 T1D human patients did not show any differences in their markers of mineral apposition or bone structure (18).…”
Section: Altered Bone Turnovermentioning
confidence: 99%